Students' Scientific Literacy in Chemistry Learning through Collaborative Techniques as a Pillar of 21st-Century Skills - Carlina Anggraeni; Anna Permanasari; Leny Heliawati (Yayasan Keluarga Guru Mandiri, 2022)
This study aims to measure students' scientific literacy and collaboration skills. The method used was survey research on 267 high school students in Jakarta. The instrument in this study was a scientific literacy test of 40 multiple-choice PISA items developed by Moore and Foy (1997) and a non-test instrument in a rubric observation sheet to measure students' collaboration skills. The results show that students' scientific literacy is at a moderate level. Of 27 students, there are 3% of students with very high scientific literacy skills, 7% of students with high scientific literacy skills, 64% of students with moderate scientific literacy skills, 11% of students with low scientific literacy skills, and 15% of students with very low scientific literacy skills. The research concludes that scientific literacy is a skill that students must possess. Scientific literacy and collaboration skills are needed to face the demands of 21st-century learning with the rapid development of technology and knowledge.